Sulfur Redox Reactions at Working Interfaces in Lithium–Sulfur Batteries: A Perspective - Yuan, Hong; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Qiang (Advanced materials interfaces, 2019)
Lithium–sulfur (Li–S) batteries have been strongly considered as one of the most promising future energy storage systems because of ultrahigh theoretical energy density of 2600 Wh kg−1. The natural abundance, affordable cost, and environmental benignity of elemental sulfur constitute additional advantages. However, complicated reaction behaviors at working electrode/electrolyte interfaces that involve multiphase conversion and multistep ion/electron diffusion during sulfur redox reactions have impeded the thorough understanding of Li–S chemistry and its practical applications. This perspective article highlights the influence of the ion/electron transport and reaction regulation through electrocatalysis or redox mediation at electrode/electrolyte interfaces on various interfacial sulfur redox reactions (liquid–liquid–solid interconversion between soluble lithium polysulfide with different chain lengths and insoluble lithium sulfides in liquid‐electrolyte Li–S batteries and direct solid–solid conversion between sulfur and Li2S in all‐solid‐state Li–S batteries). The current status, existing challenges, and future directions are discussed and prospected, aiming at shedding fresh light on fundamental understanding of interfacial sulfur redox reactions and guiding the rational design of electrode/electrolyte interfaces for next‐generation Li–S batteries with high energy density and long cycle life. Sulfur redox reactions at working interfaces are very crucial for efficiently operating lithium–sulfur batteries. In this perspective article, focusing on the interfacial conversion processes of sulfur, current status and future directions are included to shed light on an in‐depth fundamental understanding of interfacial behavior for sulfur electrochemistry toward better lithium–sulfur batteries.